Pengaruh Love Language Terhadap Keharmonisan Pada Pasangan Remaja Di Kota Yogyakarta - Cicilia Levina Putri Jelita; Ryan Apriliano Wijaya; Fallum Falfadiga Syef Afgatan (CV. ITTC INDONESIA, 2025)
Romantic relationships among adolescents are often influenced by the way they express and receive affection. Understanding love languages ​​is key to strengthening relationships and increasing emotional satisfaction. The purpose of this study was to explore the impact of love languages ​​on the harmony of young couples in Yogyakarta. Through a quantitative survey approach, data were collected from 100 participants aged between 17 and 24 years using a structured questionnaire. The results of the analysis showed that